Real Convergence, Price Level Convergence and Inflation Differentials in Europe - Balázs Égert (Oesterreichische Nationalbank (OeNB), 2007)
This paper provides a comprehensive review of the factors that can cause price levels to diverge and which are at the root of different inflation rates in Europe including the EU-27. Among others, we study the structural and cyclical factors influencing market and non-market-based service, house and goods prices, and we summarise some stylised facts emerging from descriptive statistics. Subsequently, we set out the possible mismatches between price level convergence and inflation rates. Having described in detail the underlying economic factors, we proceed to demonstrate the relative importance of these factors on observed inflation rates first in an accounting framework and then by relying on panel estimations. Our estimation results provide the obituary notice for the Balassa-Samuelson effect. Nevertheless, we show that other factors related to economic convergence may push up inflation rates in transition economies. Cyclical effects and regulated prices are found to be important drivers of inflation rates in an enlarged Europe. House prices matter to some extent in the euro area, whereas the exchange rate plays a prominent (but declining) role in transition economies.
Keywords: E43; E50; E52; C22; G21; O52; 330; price level; inflation; Balassa-Samuelson; tradables; house prices; regulated prices; Europe; transition